Exploration of how the molecular structure surrounding the β-dicarbonyl group impacts formation of brominated haloacetic acids - Grundy, Polly; Jarvis, Peter; Fawell, John; Campo Moreno, Pablo; Goslan, Emma H.; Haley, John A.; Jefferson, Bruce (Royal Society of Chemistry (RSC), 2026)
Disinfection by-products (DBPs) are formed during the chlorination of drinking water and present a risk to human health, with brominated DBPs identified as more toxic than their chlorinated analogues. The most widely regulated DBPs are trihalomethanes (THMs), but increasingly focus is on haloacetic acids (HAAs), including consideration of all nine brominated and chlorinated HAAs for regulation (HAA9). Recently, aliphatic carbonyl compounds have been recognised as important DBP precursors and to favour bromine incorporation. This research specifically focuses on smaller aliphatic carbonyl precursors, enabling identification of the molecular-level features that are most significant for increasing the risk of forming the more toxic brominated DBPs and for reducing compliance with potential HAA9 regulations. This showed that β-keto acids present a particular problem due to their high propensity for bromination and Br-HAA formation. However, in the context of HAA9 standards, the neutral ester compounds were equally significant due to formation of the mixed chlorinated and brominated bromochloroacetic acid, which is within the currently unregulated HAAs. The enhanced understanding of Br-DBP formation from such hydrophilic organic precursors is important as such compounds are poorly removed by standard coagulation water treatment and are formed during oxidative treatment processes. Consequently, source waters containing these compounds and bromide are at significant risk of forming unacceptable levels of HAA9, a problem which becomes increasingly urgent as pressure on resources forces reliance on poorer quality drinking water sources containing higher levels of bromide. Further, the work shows that current monitoring approaches are inadequate when we need to consider HAA9.
Keywords: 34 Chemical Sciences; 3407 Theoretical and Computational Chemistry; Generic health relevance